EDUKASI LITERASI KEUANGAN UNTUK MENINGKATKAN PERSONAL INCOME BAGI PEKERJA KONSTRUKSI DI KECAMATAN SUKOLILO, KOTA SURABAYA - Tsumma Lazuardini Imamia; Sutrisno Sutrisno; Atik Andhayani; Novrida Qudsi Lutfillah; Rita Darmayanti; Atika Syuliswati; Nurafni Eltivia (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
Construction workers, as the main pillar of infrastructure development, often face challenges in managing their finances. Income fluctuations, urgent living needs, and lack of access to formal financial products and services are the main obstacles. This community service aims to improve the understanding of financial literacy among construction workers in Sukolilo District, Surabaya by implementing simple financial management. The activity method used is Focus Group Discussion (FGD). Furthermore, a SWOT analysis is carried out to enable the identification of actions that need to be taken to utilize potential and improve deficiencies, as well as to adapt to changes that may occur. The programs implemented include interactive training, individual consultations, and the provision of easy-to-understand educational materials. The training materials cover a variety of topics, from budget planning, debt management, to simple investments. The results of this community service show a significant increase in the level of financial literacy of participants. This is reflected in the increased ability of participants to prepare budgets, record expenses, and make wiser financial decisions. In addition, this program can also direct participants' financial behavior to improve savings habits and reduce dependence on high-interest loans. This financial literacy program for construction workers proves that with the right approach, we can empower them to achieve financial well-being. Through strong synergy, we can build a better future for construction workers and their families.